CLINICAL MANAGEMENT AND COMPREHENSIVE SURGICAL RESOLUTIONS OF INFECTED RIGHT PREAURICULAR FISTULA IN A PEDIATRIC PATIENT - M.Rifki Kholis P; M.Abduh Firdaus (Jurnal Kesehatan Siliwangi, 2025)
Introduction : Congenital preauricular fistula (CPF) is a common external ear anomaly resulting from the fusion failure of the six hillocks of His during embryological development. While often asymptomatic, these epithelial-lined tracts are prone to recurrent infections and abscess formation, necessitating appropriate pharmacological and surgical intervention to prevent recurrence. Purpose : This case report details the successful two-stage management—initial medical control of infection followed by definitive surgical excision using the supra-auricular approach—of an infected congenital preauricular fistula in a 10-year-old boy, emphasizing strategies to minimize recurrence. Case Report : A 10-year-old boy presented with throbbing pain and swelling in the right preauricular area for one month, worsening over the last three days. Physical examination revealed a congenital fistula orifice with a fluctuant mass measuring 1 cm x 1 cm, which was hyperemic and tender, accompanied by a history of fever. The patient was diagnosed with an infected right preauricular fistula. Management included Cefixime, Methylprednisolone, and Paracetamol for infection and inflammation control, followed by a planned fistulectomy during the quiescent phase.8 Discussion : The primary challenge in CPF management is the high recurrence rate, ranging from 0% to 42%, often caused by incomplete tract excision. The use of the supra-auricular approach (SAA) has been shown to significantly reduce recurrence rates compared to simple sinectomy by providing broader visualization of the fascial and cartilaginous borders. Controlling acute infection with broad-spectrum antibiotics and corticosteroids is crucial to minimize tissue edema and clarify dissection planes during surgery. Conclusion : Successful resolution of a preauricular fistula requires a staged approach starting with aggressive control of acute infection followed by definitive surgical excision during the quiescent period. The SAA technique, use of magnification, and excision of a portion of the helical cartilage are highly recommended to minimize the risk of recurrence.